2017
DOI: 10.1080/09589236.2017.1388220
|View full text |Cite
|
Sign up to set email alerts
|

Young men’s friendships: inclusive masculinities in a post-university setting

Abstract: When Eric Anderson published inclusive masculinity theory (IMT), it was largely situated in relationships he observed with first-year undergraduate students. Here, he noticed a striking difference in behaviors and attitudes between the adolescent heterosexual men in the United States, compared to those in the UK. Since IMT's inception, there has been a great deal of further inquiry into the social lives of young heterosexual men in both of these nations. What is undertheorized, however, is whether the intense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…A voluminous research literature has followed, highlighting the increased openness and affection among friends and greater acceptance of sexual difference among schoolboys (e.g. McCormack, 2012), undergraduate young men (Robinson et al, 2017), YouTube gamers (Maloney et al, 2018) men who have long left educational settings (Magrath and Scoats, 2019), and even elderly men (Anderson and Fidler, 2018).…”
Section: Masculinity and Homosocial Bondingmentioning
confidence: 99%
“…A voluminous research literature has followed, highlighting the increased openness and affection among friends and greater acceptance of sexual difference among schoolboys (e.g. McCormack, 2012), undergraduate young men (Robinson et al, 2017), YouTube gamers (Maloney et al, 2018) men who have long left educational settings (Magrath and Scoats, 2019), and even elderly men (Anderson and Fidler, 2018).…”
Section: Masculinity and Homosocial Bondingmentioning
confidence: 99%
“…This level of emotional vulnerability is in direct contrast to traditional masculinity norms that require men to be stoic and resist sharing feelings and emotions, particularly with another man (Courtenay, 2000). Emotional intimacy was identified in 23 of the studies (Adams, 2011;Anderson, 2008Anderson, , 2011Anderson, , 2012Anderson & McGuire, 2010;Blanchard et al, 2017;Brandth & Kvande, 2018;Caruso & Roberts, 2018;Fine, 2019;Finn & Henwood, 2009;Gottzén & Kremer-Sadlick, 2012;Henwood & Procter, 2003;Jóhannsdóttir & Gíslason, 2018;Johansson, 2011;Lee & Lee, 2018;Magrath & Scoats, 2019;McCormack, 2011;McCormack, 2014;Morales & Caffyn-Parsons, 2017;Morris & Anderson, 2015;Roberts et al, 2017;Robinson et al, 2018;White & Hobson, 2017). Anderson (2011) described participants hugging and comforting each other openly when sad or upset.…”
Section: Emotional Intimacymentioning
confidence: 99%
“…The Global Theme of Inclusivity relates to the participants' acceptance of homosexuality, decreasing levels of homophobia, as well as decreasing levels of misogyny, and a general desire for gender equality. Twenty-four of the 33 studies reported that the participants displayed decreased levels of homophobia (Adams, 2011;Anderson, 2008Anderson, , 2011Anderson, , 2012Anderson et al, 2019;Anderson & McCormack, 2015;Anderson & McGuire, 2010;Blanchard et al, 2017;Caruso & Roberts, 2018;Drummond et al, 2014;Fine, 2019;Hall et al, 2012;Jarvis, 2013;Jóhannsdóttir & Gíslason, 2018;Magrath & Scoats, 2019;McCormack, 2011McCormack, , 2014Morales & Caffyn-Parsons, 2017;Morris & Anderson, 2015;Pfaffendorf, 2017;Roberts et al, 2017;Robinson et al, 2018;Scoats, 2017;White & Hobson, 2017). This ranged from what was described as shifting attitudes toward homosexuality (Jarvis, 2013), to the complete absence of homophobia (Morales & Caffyn-Parsons, 2017).…”
Section: Inclusivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively new concept in masculinity studies is what is termed "inclusive masculinity theory" (Anderson, 2010a(Anderson, , 2010bAnderson & McGuire, 2010). The most recent article we could find stating the key outlines of the theory does not mention disability at all (Anderson & McCormack, 2018), nor does disability tend to be mentioned in debates on this supposedly "inclusive" theory (see, for example, De Boise, 2015; Magrath & Scoats, 2019;O'Neill, 2015;Scoats, 2017). For people who work in the field of disability studies, the word "inclusive" almost always implies including everybody, with people with disabilities being a key part of that inclusion (as in the term "inclusive education").…”
mentioning
confidence: 99%